Jackfruit Seed-Derived Nanoporous Carbons as the Electrode Material for Supercapacitors - Rashma Chaudhary; Subrata Maji; Rekha Goswami Shrestha; Ram Lal Shrestha; Timila Shrestha; Katsuhiko Ariga; Lok Kumar Shrestha (C, 2020)
Hierarchically porous activated carbon materials from agro-waste, Jackfruit seeds are prepared by a chemical activation method involving the treatment with zinc chloride (ZnCl2) at different temperatures (600–1000 °C). The electrochemical supercapacitance performances of the prepared materials were studied in an aqueous electrolyte (1 M sulfuric acid, H2SO4) in a three-electrode system. Jackfruit seed carbons display nanoporous structures consisting of both micro- and mesopore architectures and they are amorphous in nature and also contain oxygenated surface functional groups, as confirmed by powder X-ray diffraction (pXRD), Raman scattering, and Fourier-transformed infrared (FTIR) spectroscopy, respectively. The surface areas and pore volumes were found to be 1216.0 to 1340.4 m2·g−1 and 0.804 to 1.144 cm3·g−1, respectively, demonstrating the better surface textural properties compared to the commercial activated carbons. Due to the high surface area, large pore volume, and well developed hierarchical micro- and mesoporosity, the optimal sample achieved a high specific capacitance of 292.2 F·g−1 at 5 mV·s−1 and 261.3 F·g−1 at 1 A·g−1 followed by outstanding high rate capability. The electrode sustained 71.6% capacity retention at a high current density of 20 A·g−1. Furthermore, the electrode displayed exceptional cycling stability with small capacitance loss (0.6%) even after 10,000 charging–discharging cycles, suggesting that Jackfruit seed would have potential in low-cost and scalable production of nanoporous carbon materials for supercapacitors applications.